PROFITABILITY OF PHOTOVOLTAICS IN POLAND: CASE STUDY OF A HOUSEHOLD - Łączkowska, Martyna; Borychowski, Michał (Acta Scientiarum Polonorum. Oeconomia, 2022)
Photovoltaics is increasingly used to convert solar energy into electricity in households, including in Poland. The development of this type of renewable energy results, on the one hand, from legal regulations related to climate and energy policies, and on the other hand, from the numerous benefits connected with the use of photovoltaics. These include both economic and environmental advantages. The aim of the work was to assess the profitability of installing photovoltaics in a Polish household in 2019–2021. Therefore, the costs of the investment are presented, as well as the benefits, mainly in economic terms. Different calculations and estimates concerning return on the invested capital are also shown. During the 31 months covered by the study, the cumulative positive balance of electricity that was generated above the energy consumed in the household exceeded 2,900 kWh, which resulted in an economic surplus of over PLN 1,600 (about EUR 360). What is more, the investment contributed to the protection of the natural environment which is the added value of the photovoltaics.